Supportive Periodontal Treatment and Full-mouth Ultrasonic Debridement: A Randomised Controlled Clinical Trial - Ueda, Paulo Hitoshi [UNESP]; Casati, Marcio Zaffalon [UNESP]; Viana Casarin, Renato Correa [UNESP]; Pera, Claudia [UNESP]; Pimentel, Suzana Peres [UNESP]; Cirano, Fabiano Ribeiro [UNESP] (Quintessence Publishing Co Inc, 2014)
Purpose: To evaluate the effect of different maintenance recall intervals in patients with chronic periodontitis treated by full-mouth ultrasonic debridement. Materials and Methods: Twenty-eight patients participated in the study and were divided into two groups: group 1 (n = 14) underwent full-mouth ultrasonic debridement followed by monthly supportive periodontal therapy; group 2 (n = 14) underwent full-mouth ultrasonic debridement followed by supportive periodontal therapy delivered at 3-month intervals. Plaque index (PI), bleeding on probing (BOP), pocket probing depth (PD), gingival recession (GR) and clinical attachment level (CAL) were evaluated at baseline and after 3 and 6 months. Results: Subjects in group 1 had statistically significantly lower PI scores than did subjects in group 2 at six months. However, no differences in BOP, PPD, GR and CAL were observed between groups at any of the time points evaluated. Nonetheless, while full-mouth BOP and PPD scores progressively decreased over time in group 1, the same parameters were significantly reduced at 3 months in group 2, but remained stable thereafter. The proportion of moderate and deep pockets decreased progressively over time in the group of monthly recalls, while the proportion of moderate to deep sites decreased significantly in group 2 only at 3 months; no additional reductions were seen at 6 months. Conclusion: Supportive periodontal therapy both at one- and three-month intervals promotes short-term stability of clinical improvements obtained after full-mouth ultrasonic debridement in patients with chronic periodontitis.
Keywords: periodontal therapy; periodontitis; ultrasonic debridement